Efektivitas Media dan Teknologi Berbasis Aplikasi dalam Pembelajaran: Sebuah Tinjauan Literatur - Dedi Harianto; Nuraisyiah; Hasyim, Sitti Hajerah; Azis, Fajriani (Nusa Putra University, 2024)
The development of information and communication technology, as well as the use of media and application-based technology in learning, has become increasingly important and necessary to facilitate the learning process. Various literature on the use of applications in the learning process and how it impacts learning effectiveness is reviewed in this study. This research employs a qualitative descriptive methodology based on a literature review. The study focuses on previous research regarding the use of learning applications across different educational levels. The review findings indicate that the use of applications can enhance student engagement, supporting independent learning, and improve educators' ability to create more accessible learning materials. However, factors such as educators' readiness to continuously enhance their skills in using technology, the availability of technological infrastructure, and the design of user-friendly learning applications also influence the success of implementation.